2018
DOI: 10.15520/ijnd.v8i04.2128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Conflict-Management Enhancing Strategy for Head Nurses on the Quality of Vertical Dyad Linkage with Nurses

Abstract: Background: Conflict management is an essential skill for an effective nurse leader. As the inappropriate use of conflict resolution skills leads to degeneration of communication and poor working relationships particularly between nurse leader and their staff nurses. Aim: The present study aimed to determine the effect of conflict-management enhancing strategy for head nurses on the quality of vertical dyad linkage with nurses. Material and methods: Pre-experimental research design (one-group pretest-posttest)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…This was consistent with Devi & Hajamohideen, (2018) (28) who clarified that most of head nurses reported that they are unable to acquire adequate supporting supervision.This was supported by Thakre et al, (2017) (29) who illustrated that most of head nurses had dissatisfaction with direct supervisor and higher nursing director and had low perception of supervisor relationships. On the contrast, these results disagree with Ibrahim et al, (2018) (30) who found that head nurses had moderate level of satisfaction at their work and respected by their supervisors.…”
Section: Discussioncontrasting
confidence: 86%
“…This was consistent with Devi & Hajamohideen, (2018) (28) who clarified that most of head nurses reported that they are unable to acquire adequate supporting supervision.This was supported by Thakre et al, (2017) (29) who illustrated that most of head nurses had dissatisfaction with direct supervisor and higher nursing director and had low perception of supervisor relationships. On the contrast, these results disagree with Ibrahim et al, (2018) (30) who found that head nurses had moderate level of satisfaction at their work and respected by their supervisors.…”
Section: Discussioncontrasting
confidence: 86%
“…Dashboard., 2020 , Elshimy et al, 2002 , Ibrahim et al, 2018 , Marquis and Huston, 2015 , Robert et al, 2020 , Tan et al, April 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…and more than one third of nurses preferred collaboration style followed by accommodation style post-intervention. While Ibrahim et al [26] reported that, in the pre-training stage, it was found that more than two-thirds of the studied head nurses used accommodating strategy as a primary method to resolve conflict followed by compromising strategy. Meanwhile, in the post implementation stage, 45.2% of the studied head nurses used accommodating strategy as a primary method to resolve conflict followed by 9.7% of them used avoiding and compromising strategies to resolve conflict.…”
Section: Discussionmentioning
confidence: 93%
“…In the same line, Said Ahmed & El Demerdash [25] who conducted a study entitled "An Educational Program about Nursing Managers' Transformational Leadership, Conflict Management Styles and Decision Making Effectiveness" reported that the levels of nursing managers' total knowledge regarding transformational leadership and conflict management were significantly improved post-educational program. Also Ibrahim et al [26] who conducted a study entitled "The Effect of Conflict-Management Enhancing Strategy for Head Nurses on the Quality of Vertical Dyad Linkage with Nurses" stated that there was a statistically significant improvement in head nurses' knowledge regarding conflict and its management strategies after strategy implementation.…”
Section: Discussionmentioning
confidence: 99%